Rancang Bangun Sistem Informasi Pemesanan dan Distribusi Makan Pasien Rawat Inap Berbasis Web (Studi Kasus: RSUD Cengkareng) - Taufiq, Rohmat; Priyanggodo, Dyas Yudi; Daniarti, Yeni; Teddy Risnayadi (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The hospital’s hospitalized patient food ordering service is an important component and process that is not separated from the patient’s healing process during the hospitalization treatment, which is to provide quality and fast food menu to achieve optimal nutrition status. Currently, the process of recording food orders and reporting data in the nutrition installation of Cengkareng Hospital is still done manually and not fully computerized, which has drawn criticism because it is considered slow in the process of managing food orders and reporting data. This research aimed to create an inpatient food ordering information system that could help medical staff and nutritionists in the food ordering process, increase time and energy efficiency, and provide accurate and real-time data reporting. This research method applied data collection methods through observation, interviews, and literature studies. The design method focuses on developing models using the UML (Unified Modeling Language) model such as Use case diagrams. Sequence Diagrams, Activity Diagrams and Class Diagrams. In software development, the method used is the waterfall method. This system was built using PHP programming language with SM framework and PostgreSQL database and testing using the black box method.